« Motionless Monotony »: New Nowheres in Irish Photography - Colin Graham (Revue LISA)
In recent years the psychogeography of Ireland has shrunk. Places are closer together because the distances between them take less time to traverse. In this process of acceleration and psychic contraction the marks and traces of road-building and faster human movement necessitate the appearance of new landscapes, strips of nowhere places; verges, wastelands, unfinished building sites, ‘open’ areas, suburban spaces. This paper will trace a journey in and around Dublin, and then into the midlands of Ireland, following photographers who have travelled in and catalogued these new Irish nowheres. Their work can be seen as akin to the methodology of the “psychogeographic” walking and writings of Iain Sinclair, its intent being “to vandalise dormant energies by an act of ambulant signmaking.” This fascination with dead space inhabited by living people will be discussed in recent projects by Anne Cleary and Denis Connolly (Moving Dublin), Mark Curran (Southern Cross), Dara McGrath (By the Way), Simon Burch (Under a Grey Sky), Martin Cregg (Midlands) and Jackie Nickerson (Ten Miles Round). The paper will examine the ways in which these photographic projects seek out the traces and marks of human activity, even when it is part of the eradication of the landscape, and find these traces to be the marks of presence. They are thus places of hope and despair and are the warning signs of the proliferation of what Marc Augé calls “non-places.” This journey in photographic landscapes is then a narrative of the physical erosion of an old Ireland and a set of questions about the fate of a future Ireland.